Analysis of Frames with and Without Knee Bracing for Lateral Loads Using Steel Structures - K, Kanishkavya; D, Sivakumar; M, Velumani (International Research Journal of Multidisciplinary Technovation, 2019)
Steel has become the predominate material for the construction of bridges, buildings, towers and other structures. Its great strength, uniformity light weight and many other desirable properties makes steel the material of choice for numerous structures such as steel bridges, high rise buildings, towers and other structures. The advantages in general credited to steel as a structural design material are high strength/weight ratio, ductility, predictable material properties, speed of erection structures, and quality of construction ease of repair, adaptation of prefabrication, repetitive use, expanding existing structures and fatigue strength. Steel structures should be stiff enough to limit the drift and should have enough ductility to prevent collapse. In this steel bracing provides an effective and economical solution for resisting lateral loads in a framed structure. Knee braced steel frame is that of excellent ductility and lateral stiffness. Since the knee element is properly fused, yielding occurs only to the knee element and no damage to major elements In this study, the effect of different types of bracing in comparison with knee braced steel frame are studied and analysed using software.